A Fully Automatic Stitching of 2D X-ray Images - Mateika, D.; Martavičius, R. (Elektronika ir Elektrotechnika, 2007)
Problems of the stitching one big image out of several smaller image fragments are being solved in this paper. Proposed methodic, for the fully automatic stitching of two-dimensional computer radiographs. Methodic is based on the requirement to have additional information about scale and rotation angle in the image fragments to be stitched. Proposed to add marker information into radiograph, by placing a sturdy metal strip having rectangular holes, near the object being observed, during image fragment registration. The method allows identifying image parameters required for the seamless stitching according to the rectangular holes detected from the strip shape and joining image fragments in a fully automatic manner. Method implementation is described. Problems of the fragment parameters’ – rotation angle, scale and disposition identification are being solved. Presented algorithm for radiographs rotation angle calculation using Fourier transform and its verification results. Ill. 10, bibl. 9 (in English; summaries in English, Russian and Lithuanian).